Case Report: Reversal of Hyaluronic Acid Rectal Wall Infiltration with Hyaluronidase - Hong, Anne; Ischia, Joseph; Chao, Michael (Frontiers in Oncology, 2022)
Peri-rectal spacers provide protection to the rectum for patients receiving radiation therapy treating prostate cancers. Commonly used hydrogel spacers hold the disadvantage that they cannot be readily reversed should inadvertent injection outside of the target area occur, potentially leading to ischemia of the rectal mucosa leading to severe pain and ulceration, which can then lead to superinfection and pelvic abscess formation, and subsequently recto-prostatic fistulas. This could require major surgical intervention. New hyaluronic acid spacers are readily reversible with hyaluronidase and provide a valuable means to correct any misinjected spacer. We present a patient with prostate cancer who was planned for radiation therapy and required a rectal spacer. The hyaluronic acid rectal spacer was injected in part into the rectal wall. The patient was asymptomatic and a sigmoidoscopy confirms healthy bowel mucosa only. The misinjected hyaluronic acid was successfully treated with targeted injection of hyaluronidase into only the rectal wall portion. Serial follow up imaging demonstrated rapid dissolution of the misinjected hyaluronic acid with the well positioned hyaluronic acid remaining. The patient did not experience any side effects of the hyaluronidase.